Governance, not design, rules European Atlantic MPA performance - Álvarez Fernández, Inmaculada (2024)
We studied 125 NE Atlantic Marine Protected Areas (MPA) managed by 56 management plans (MgP) to test the hypothesis that MgP design and implementation and governance processes affect MPA performance using 8 indicators characterizing these processes (MgP objectives, MgP stakeholders, MgP implementation and renewal, management effort, management quality, MPA monitoring, MPA resources and MPA management performance). Effective governance is critical for MPA performance, contradicting previous studies that identified MPA design, MgP design, and stakeholder participation as key factors. The quality of management was strongly dependent on the correct effort and resource allocation; excessive focus on budget and law enforcement, which reduced other efforts, was negative for performance. Contrarily, investment in other tasks (operative management body, monitoring and assessment, information, education and communication, and community participation) increased performance. Good MgP design and implementation had limited effects. Conversely, high management quality (including continuous knowledge generation and improvement) could increase performance independently of an adequate design in the early stages. Our results suggest the need to revise the rationale of public MPA policies in Europe.